Prognosis of patients with breast cancer who underwent breast-conserving surgery using a 3D-printed surgical guide after neoadjuvant chemotherapy - Ah Yoon Kim; Sae Byul Lee; Tae Kyung Yoo; Ji Sun Kim; Il Yong Chung; Hee Joung Kim; Jong Won Lee; Byung Ho Son; Jae Ho Jeong; Hee Jin Lee; Nam kug Kim; BeomSeok Ko (Scientific Reports)
Abstract In breast-conserving surgery (BCS), clear resection margins are crucial to prevent recurrence. Accurate imaging is vital for precise BCS, with MRI being the most accurate. However, MRI has limitations in identifying the exact extent of breast cancer in patients who have undergone neoadjuvant chemotherapy (NACT). A 3D-Printed Breast Surgical Guide (3DP-BSG) can address this issue by effectively pinpointing cancer extent in NACT patients, thus enhancing surgical accuracy. This retrospective single-institution cohort study focused on female patients diagnosed with invasive breast cancer who underwent NACT. Between November 2015 and October 2021, patients received BCS with the aid of a 3DP-BSG. Personalized 3DP-BSG targeted tumors by tracking changes in breast and tumor anatomy on MRI before and after NACT. 203 patients with invasive breast cancer were enrolled in the study. According to exclusion criteria, 197 patients were analyzed. The median follow-up period was 35.3 months (range: 2.2–96.8 months). 3 patients (1.5%) had positive resection margins. During the follow-up period, 17 patients (8.6%) experienced recurrence, with one patient (0.5%) confirmed local recurrences. The application of MRI-based 3DP-BSG is effective in achieving low positive margins and local recurrence in patients undergoing BCS after NACT, offering a promising approach for improving surgical outcomes.